Visual Narratives for Local Development. Uderstanding Local Restoration through Local Place Branding: an Italian Case - De Salvo, Paola; Pizzi, Marco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Place Branding is a theoretical, economic and public policies that needed many years to be gradually acknowledged and told apart by Place Marketing. The academics that dealt with the production and distribution of the places’ image, as matter of fact, often did it with a marketing-oriented approach, trying to measure how and many tourists, investors and new inhabitants were attracted by specific communications campaigns. Over the course of time, however, Place Branding has been increasingly identified as a more complex and multidimensional theme. By the end of this point of view changing process, Place Branding was not only and independent matter of study, but also was comprehending Place Marketing as an ancillary component. The Place Branding, indeed, has been described, during the last fifteen years, as a territorial government tool, even worthy to have specific institutional structures, too. “Participatory Place Branding” and “Public Branding” theories, at last, describe Place Branding also in its most social aspects and contemplate the need of participation during the local image management processes. Place Branding, in conclusion, can be now considered an independent matter of study and policies, which needs to develop new strategies to involve all the stakeholders in the local promotion process. The emancipation of Place Branding, however, still requires to overcome the common prejudice that links it to the commodification of spaces, which pushes some disciplines not to consider it an interesting study object in local development studies. To do so, it is necessary to address more precisely how the narratives about a place influence its development and to understand how the local development dimensions interact with the actions related to local Place Branding. This article wants to contribute to expand the knowledge about the connection between Place Branding and local development. It will try to do so using a still under-exploited methodology for this kind of studies, that is the visual content analysis as described by Bell (2000) and Parmeggiani (2011). This methodology will be applied to a dataset of pictures in the tourism context, taking in consideration that, even tourism has a certain tradition in visual studies, it often has been addressed to mere economic aims. Tourism visual narratives will be also considered as an important source of data because of the great importance that Anholt (2007) attaches to it as communication channel of a place. The research will consist of a comparison between different narrative lines about the same rural village of Central Italy, Postignano. It is a deserted hamlet bought by a private company that wants to make it live again attracting new inhabitants, tourists and investors, but also connecting it with the surrounding territory. This project, naturally, is taking place within an Italian region – Umbria – that already has its own active narrative on places like this one – that are a specific characteristic of its territory – and it could be interesting compare what are the similarities and differences between the different narratives activated by these entrepreneurs and the regional government. Another under-valuated narrative will be produced and considered for this article, that is the local inhabitants’ one. Using the photo elicitation technique, indeed, a further comparison will be made, with the aim to underline what are the characteristics of the territory that have not been considered during its promotion. Visual content analysis of different narratives produced by Place Branding in tourism field can give useful hints about what is excluded by place branding and about many potentialitiesthat can be carried out. This approach, indeed, is a way to confront different points of view, opinions and desires on the many different possible development paths that a place can choose.